Knowledge of antenatal care among mothers of infants in rural area of Belagavi: a cross sectional study - Sinha, Pragya; Gunagi, Praveena R.; Viveki, R. G.; Kamble, Manjunath; Halki, Sunanda (International Journal Of Community Medicine And Public Health, 2019)
Background: Antenatal care (ANC) is the care given to pregnant women for safe pregnancy and healthy babies. It is the most effective health intervention for preventing maternal morbidity and mortality. Health knowledge is an important element which enables women to be aware of their health status and promotes service utilization which further improves the health of the beneficiaries. This study was conducted among mothers of rural area of Belagavi with an objective to determine the level of knowledge related to ANC and the factors associated with the same. Methods: A cross-sectional study was carried out in February-April 2018 among mothers who had delivered within one year from date of study and who had registered and availed antenatal services in field practice area of Department of Community Medicine, BIMS, Belagavi. Sample size was calculated as 161. Mothers were selected using systematic sampling. Data was collected after obtaining an informed, written consent from the participants and was compiled, tabulated and analysed in MS Excel. The results are presented as percentage and proportions and chi square test has been applied. Results: 50% participants had fair knowledge regarding ANC. The level of knowledge was found to be statistically significant with employment status and BPL status. Conclusions: The study found adequate knowledge among majority of mothers.